Penerapan Rehabilitasi Terhadap Penyalahgunaan Narkotika Oleh Badan Narkotika Nasional Kota Surakarta - Tambunan, BIntang Krins; -, Supanto (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
This study aims to determine the urgency of the implementation of rehabilitation by the National Narcotics Agency against narcotics users in eradicating narcotics abuse and illicit drug trafficking in Indonesia. This research is normative legal research, prescriptive in nature, using primary and secondary legal materials, which are analysed using a deductive logic reasoning method. The technique of collecting legal materials used is called literature study. To support the legal chart, interviews were conducted with the Surakarta City National Narcotics Agency. The results showed that the implementation of rehabilitation for narcotics users has not been fully implemented in accordance with what has been regulated in Article 54 of Law Number 35 of 2009 concerning Narcotics. In this study, an inventory of legal instruments was also carried out with the basic rules of the Law Number 35 of 2009 concerning Narcotics and the rules below. From these regulations, it has been regulated about the obligation to carry out rehabilitation and the mechanism for implementing the rehabilitation of a person if proven to be a narcotics user. But there are still cases that give prison sentences to narcotics users. As narcotics users are people who are sick both physically and psychologically, rehabilitation is intended for narcotics users to cure narcotics users from dependence on narcotics.